2021
DOI: 10.1088/1361-6528/ac4130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of B/N co-doping on electrical and photoluminescence properties of CVD grown homoepitaxial diamond films

Abstract: Boron doped diamond (BDD) has great potential in electrical, and electrochemical sensing applications. The growth parameters, substrates, and synthesis method play a vital role in the preparation of semiconducting BDD to metallic BDD. Doping of other elements along with boron (B) into diamond demonstrated improved efficacy of B doping and exceptional properties. In the present study, B and nitrogen (N) co-doped diamond has been synthesized on single crystalline diamond (SCD) IIa and SCD Ib substrates in a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…The presence of C-O species on the pristine CFE is due to surface contamination and partial oxidation in the air atmosphere. These results agree with the literature findings (Sobaszek et al, 2016;Kunuku et al, 2022). The oxidised to non-oxidised carbon share, C ox = 0.40 for pristine CFE, is based on C 1s spectral deconvolution.…”
Section: Carbon Felt Electrodes Surface Characterisationsupporting
confidence: 92%
“…The presence of C-O species on the pristine CFE is due to surface contamination and partial oxidation in the air atmosphere. These results agree with the literature findings (Sobaszek et al, 2016;Kunuku et al, 2022). The oxidised to non-oxidised carbon share, C ox = 0.40 for pristine CFE, is based on C 1s spectral deconvolution.…”
Section: Carbon Felt Electrodes Surface Characterisationsupporting
confidence: 92%
“…The co-doping of boron and oxygen has been widely investigated by many groups. [13][14][15] For example, Issaoui et al [16] have studied the effect of oxygen on the heavily boron-doped diamond and shown that the obtained films exhibit high crystalline quality with adding a large amount of oxygen in gas phase. However, most of the prior literature focuses on the effect of oxygen on the properties (such as crystalline quality, [17,18] growth rate, [18,19] and electrical property [17,19] ) in heavily boron-doped diamond.…”
Section: Introductionmentioning
confidence: 99%